Investigation of low-frequency noise of 28-nm technology process of high-k/metal gate p-MOSFETs with fluorine incorporation. (January 2016) - Kao, Tsung-Hsien; Chang, Shoou-Jinn; Fang, Yean-Kuen; Huang, Po-Chin; Wang, Bo-Chin; Wu, Chung-Yi; Wu, San-Lein
Highlights: LFN characteristics of HK/MG pMOSFETs from a 28-nm bulk CMOS technology. We investigated the properties of dielectric traps by the impact of F implantation. We establish the relationship between the trap depth in RTN and λ in the 1/ f noise. F implantation could result in a smaller λ and smaller slow Nt . Abstract: In this study, the properties of dielectric traps by the impact of Fluorine (F) implantation on 1/ f noise and the random telegraph noise (RTN) of high-k/metal gate (HK/MG) p-type metal–oxide–semiconductor field-effect transistors (pMOSFETs) were investigated. The incorporation of F has been identified as an effective method to passivate oxygen vacancies, defect sites, and reduce the gate leakage current in pMOSFETs. Compared with a control device, the F-implanted HK/MG devices show that the trap positions were closer to the SiO2 interfacial layer (IL)/Si channel. Furthermore, we found that F implantation could result in a smaller tunneling attenuation length ( λ ) and smaller slow oxide interface trap density ( Nt ).